ECOFRIENDLY ADSORBENT FROM FOOD WASTE FOR WATER PURIFICATION - Kumari, K.S. Beena; Paulin, S. Mary (International Journal of Research -GRANTHAALAYAH, 2021)
Egg shell, which is a waste material emerging out in large quantities from poultries, homes and restaurants, may be used as a good adsorbent for heavy metals. Different types of eggshells were used in this study for the adsorption of a major pollutant such as iron from surface water. Effect of CaCO3 content in the egg shell, particle size, contact time, temperature and shaking on adsorption were also studied. The adsorption isotherms fitted by the Langmuir model revealed that the adsorption of iron by eggshell samples was monolayer adsorption.